1999
DOI: 10.1161/01.cir.99.9.1190
|View full text |Cite
|
Sign up to set email alerts
|

Acute Saline Infusion Reduces Alveolar-Capillary Membrane Conductance and Increases Airflow Obstruction in Patients With Left Ventricular Dysfunction

Abstract: Background-Impaired alveolar-capillary membrane conductance is the major cause for the reduction in pulmonary diffusing capacity for carbon monoxide (DLCO) in heart failure. Whether this reduction is fixed, reflecting pulmonary microvascular damage, or is variable is unknown. The aim of this study was to assess whether DLCO and its subdivisions, alveolar-capillary membrane conductance (DM) and pulmonary capillary blood volume (Vc), were sensitive to changes in intravascular volume. In addition, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 46 publications
4
46
0
4
Order By: Relevance
“…25 Conversely, infusion of 10 ml/kg of saline into 10 patients with a left ventricular ejection fraction (LVEF) <40% resulted in a fall in forced expiratory volume in 1 s (FEV1), forced expiratory ratio (FER) and diffusing capacity for carbon monoxide (DLCO). 26 The same study also demonstrated lower baseline FEV1, FVC and DLCO in these subjects compared with a control group. Studies of patients undergoing acute hospitalisation for HF demonstrated increased pulmonary resistance and reduced compliance 27 as well as reductions in FEV1, FVC and TLC but no change to DLCO compared to follow up testing.…”
Section: Effects Of Hf On Respiratory Function Testingmentioning
confidence: 68%
“…25 Conversely, infusion of 10 ml/kg of saline into 10 patients with a left ventricular ejection fraction (LVEF) <40% resulted in a fall in forced expiratory volume in 1 s (FEV1), forced expiratory ratio (FER) and diffusing capacity for carbon monoxide (DLCO). 26 The same study also demonstrated lower baseline FEV1, FVC and DLCO in these subjects compared with a control group. Studies of patients undergoing acute hospitalisation for HF demonstrated increased pulmonary resistance and reduced compliance 27 as well as reductions in FEV1, FVC and TLC but no change to DLCO compared to follow up testing.…”
Section: Effects Of Hf On Respiratory Function Testingmentioning
confidence: 68%
“…In fact, it has been shown that acute infusion of 1-2 l saline can increase pulmonary capillary blood volume by 120 % and decrease haemoglobin concentration by 17 % (Farney et al 1977), all of which leaves unchanged (Puri et al 1999) or improves lung diffusion capacity in healthy subjects (Farney et al 1977). …”
Section: Figurementioning
confidence: 99%
“…According to the basic experimental evidence that pulmonary interstitial fluid accumulation is secondary to a dysregulation of Na+ handling, changes in Dm following saline infusion have been investigated in patients with chronic HF of varying severity. In a study performed in post-MI patients with normal LV systolic function, an infusion of ~800 mL of saline reduced Dm by 13% 49 . In patients with mild to severe HF, a 150 ml infusion of saline produced a significant Dm reduction equivalent to 750 ml saline, whereas a 750 mL infusion of isotonic glucose solution did not decrease DLco and Dm 50 .…”
mentioning
confidence: 98%